ENVIRONMENTAL ACCOUNTING AS A BUSINESS MANAGEMENT TOOL - Moscoso Paucarchuco, Ketty Marilú (2020)
that seeks to formalize the care of nature throughaccounting treatment in the various economicunits, the objective of this study is to analyzeconcepts related to environmental accounting inbusiness management, which allows us to developfundamentals Theoretical and applications ofaccounting under the environmental dimension,in a descriptive way, raising awareness of theresponsibility of the accounting profession and thebusiness workforce, with fines limiting the externalitiesthat our environment gives.